A Pakistani Business Process Outsourcing (BPO) Firm’s Internationalisation Strategy for the American Market - Patel, Obaid Saleem (2012)
Internationalisation of firms, in particular tangible products exporting companies from the West to other parts of the globe, has been a well-researched topic with major contributions to this discipline coming in the forms of market entry theories (Stages theory, Transaction Cost Analysis and the Network Approach) and incentives of internationalisation. However, Service oriented Business Process Outsourcing (BPO) firms from countries like Pakistan in South Asia operating in the United States of America (US)s has certainly been an under researched area in internationalisation literature and calls for scholarly attention. This research attempts to contribute to this particular aspect of internationalisation by studying the internationalisation and competitive strategy of such a Pakistan based BPO firm (AUA Solutions) having the bulk of its clientele in the American market, by uncovering its choice and methods of market entry, analysing its source and means of competitive advantage and understanding the mechanisms its put in place to nullify the negative Country of Origin effect it faces from having a backend operation in Pakistan. This research attempts to lead the way for other researchers to explore this research area further because not only is this form of internationalisation under researched but is also inviting of large scale studies to be conducted upon it owing to the large number of such businesses actively working in Pakistan and also because they can be used as a yardstick to measure something bigger like a regional study of Pakistani, Indian and Bangladeshi firms of this nature who essentially are the biggest players of the South Asian region.